2012
DOI: 10.2166/aqua.2012.006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aquatic streptomycetes by quantitative PCR for prediction of taste-and-odour episodes in water reservoirs

Abstract: Bacteria belonging to the Streptomyces genus are known to produce several taste-and-odour compounds (TOCs), but knowledge on the abundance of streptomycetes in drinking water reservoirs and other aquatic environments is scarce. In this study, quantitative real-time polymerase chain reaction (qPCR) was applied, for the first time, to determine densities of streptomycetes in a river, at a weir and in two reservoirs in subtropical Australia. The PCR approach was optimized with respect to (a) collection of strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Using cultivation methods, densities of 10 2 to 10 5 streptomycetes l −1 were found in various freshwater environments (Lanciotti et al 2003, Lee et al 2011, while fluorescence in situ hybridization, targeting rRNA, indicated up to 2 × 10 9 cells l −1 in a water reservoir (Nielsen et al 2006). In contrast, using the present PCR approach, Lylloff et al (2012) only found up to 46 × 10 3 streptomycetes l −1 in various Australian freshwaters. Relative to these studies, the present abundance of Streptomyces in the Patuakhali ponds appears relatively high.…”
Section: Fishcontrasting
confidence: 58%
See 2 more Smart Citations
“…Using cultivation methods, densities of 10 2 to 10 5 streptomycetes l −1 were found in various freshwater environments (Lanciotti et al 2003, Lee et al 2011, while fluorescence in situ hybridization, targeting rRNA, indicated up to 2 × 10 9 cells l −1 in a water reservoir (Nielsen et al 2006). In contrast, using the present PCR approach, Lylloff et al (2012) only found up to 46 × 10 3 streptomycetes l −1 in various Australian freshwaters. Relative to these studies, the present abundance of Streptomyces in the Patuakhali ponds appears relatively high.…”
Section: Fishcontrasting
confidence: 58%
“…Densities of Streptomyces bacteria in the water were determined by quantitative PCR (TaqMan procedure) targeting the 23S rRNA gene according to Rintala & Nevalainen (2006) with the modifications given by Lylloff et al (2012). Genomic DNA was extracted from the 47 mm membrane filters after cutting each filter in 3 portions, using the PowerWater ® DNA isolation kit by Mobio (www.mobio.com) according to instructions by the producer.…”
Section: Identification Of Potential Off-flavour Producing Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then the expression of these genes has been studied in a single strain of Anabaena (Giglio et al, 2011), which was demonstrated that the expression of the geosmin gene appears to be constitutive in nature. While in recent years some studies established quantitative PCR assays to detect and measure the production of geosmin by Streptomycetes in the environment (Auffret et al, 2011;Lylloff et al, 2012); to the best of our knowledge, no peer reviewed study has displayed a quantitative PCR assay to detect the production of geosmin specifically by cyanobacteria. The present study is the first qPCR assays for the detection and quantification of the cyanobacterial geosmin synthase in waters.…”
Section: Applicability Of the Designed Primersmentioning
confidence: 99%
“…quantification of geosmin-producing Streptomyces (Auffret et al, 2011;Lylloff et al, 2012). However, the biosynthesis of geosmin by cyanobacteria has received much attention recently.…”
Section: Introductionmentioning
confidence: 99%